Kebijakan Pemerintah Indonesia Dalam Menyikapi COVID-19 Antara Pendekatan Adaptif Dan Saintifik - Irawan, Bambang; Zulkifli, Zarina; Akbar , Paisal; Loilatu, Muhammad Jafar; Ibrahim, Adil Hasan (Universitas Medan Area, 2023)
This study describes the Indonesian government's policy options in dealing with COVID-19. To explain research policy options using a scientific and adaptive approach in making policies for handling COVID-19. The Indonesian government's response to the handling of COVID-19 is considered slow due to the policy choices taken. In three years, the handling of COVID-19 has faced different policy choices and policy focuses. This study uses a qualitative approach to review government policies through a narrative policy framework analysis by selecting policies at the macro level to find out the government's steps in handling COVID-19. The findings of this study indicate that the approach used by the Government of Indonesia in handling COVID-19 tends to be adaptive. The adaptive policy is seen from the policy goals that are quite a lot that causes the handling of COVID-19 to be slow. This approach option is different from the scientific approach, which tends to have consistent goals and chooses to look at the conditions of the crisis that occurred. The use of this adaptive approach ignores the political process, which is slow and hinders the policymaking process.